The fight for faith - Amira Mohd Yunos (Nanyang Technological University, 2022)
Over the past forty years, the proportion of non-religious people in Singapore has climbed steadily, even accelerating in the past decade. The 2020 census reported that 20 per cent of the population now identifies as non-religious, up from 17 per cent in 2010. This was the greatest jump within a decade since 1980. The Buddhists and Taoists have suffered the greatest decline, as the Chinese population here grows increasingly Westernised and disconnected from Chinese culture, which is inextricably linked to these religions. Where Taoism once dominated with 30 per cent of the population, it now accounts for a meagre 8.8 per cent. Buddhism peaked in 2000 when 42.5 per cent of the population were Buddhists, but now Buddhists make up just 31.1 per cent.